Arrowheads, Axes, Ad Hoc, and Sickles: An Introduction to Aspects of Lithic Variability across the Near East in the Bronze and Iron Ages. (1st November 2013) - Rosen, Steven A.
<x xml:space="preserve">Abstract</x> Analyses of chipped stone industries in the Near East in the Bronze and Iron Ages in the past two decades have addressed major issues of evolving economic specialization, technological and functional evolution, and geographic variability. In spite of this, significant questions remain open, including explanations of geographic/functional variability between regions (especially in the distribution of projectile points), the nature and diffusion of specific technologies, such as Canaanean blades, and the regional variability in these technologies, detailed explication of the nature of production systems, and finally, better integration of the lithic systems into the larger archaeological synthesis.